2002
DOI: 10.1007/s00406-002-0380-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute placebo-controlled sleep laboratory studies and clinical follow-up with pramipexole in restless legs syndrome

Abstract: s Abstract In a single-blind, placebo-controlled crossover trial, the acute efficacy of the dopamine agonist pramipexole was investigated in 11 restless legs syndrome (RLS) patients by sleep laboratory methods, with a clinical follow-up for 4 weeks. In 3 nights (pre-treatment, placebo and drug night), objective sleep quality was determined by polysomnography (PSG), subjective sleep and awakening quality by rating scales, objective awakening quality by psychometry. Clinical follow-up consisted of completion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 40 publications
(37 reference statements)
7
55
0
2
Order By: Relevance
“…Another possibility is to substitute levodopa by a dopamine agonist, this has been shown to be successful in the case of pergolide [6] and cabergoline [7]. The therapeutic properties of the non-ergot dopamine agonist pramipexole, which has a high affinity to the D 3 receptor subtype of the D 2 family, have increasingly gained attention [8][9][10][11][12]. The first polysomnographic and placebo-controlled trial showed that a single evening dose of up to 1.5 mg pramipexole markedly alleviated sensory and motor symptoms of RLS [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is to substitute levodopa by a dopamine agonist, this has been shown to be successful in the case of pergolide [6] and cabergoline [7]. The therapeutic properties of the non-ergot dopamine agonist pramipexole, which has a high affinity to the D 3 receptor subtype of the D 2 family, have increasingly gained attention [8][9][10][11][12]. The first polysomnographic and placebo-controlled trial showed that a single evening dose of up to 1.5 mg pramipexole markedly alleviated sensory and motor symptoms of RLS [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the data obtained were subjective, after 2-3 months the majority of patients (11 of 16) reported clinically significant improvements in insomnia (Lin et al 1998). This is supported by a PSG study that demonstrated moderately improved sleep quality, although there were some changes in sleep architecture (Saletu et al 2002). Furthermore, Högl and Poewe (2005b) showed, in an RCT on 345 patients with RLS, that a single dose (0.175-0.75 mg) of pramipexole over a 24-h period significantly improved sleep compared with placebo (P=0.0001) over a 6-week period.…”
Section: Sleep Qualitymentioning
confidence: 84%
“…There is clear evidence for pramipexole on this outcome. The PSG study on 11 patients with RLS by Saletu et al (2002) Clinical trials will need to be carefully designed to clarify whether anxiety and depression are part of RLS or merely its sequelae. Studies on the effects of pramipexole on mood disturbances would also be useful to ascertain its impact on the full spectrum of consequences of RLS.…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…We found 14 studies (n = 3,197 subjects) that conformed to our inclusion criteria (Table 1). [17][18][19][20][21][22][23][24][25][26][27][28][29][30] We excluded 30 trials from analysis, including those that had an open-label design, 31-33 a cross-over design, [34][35][36][37][38] or were withdrawal studies (meaning that the effect of continuing treatment vs withdrawing treatment after a doubleblind treatment period was assessed). 39,40 In the included trials, patients received ropinirole in 7 trials (n = 1,698 subjects), 17,[19][20][21][28][29][30] pramipexole in 4 trials (n = 825 subjects), [22][23][24]27 rotigotine in 2 trials (n = 404 subjects), 18,26 and sumanirole in 1 trial (n = 270 subjects).…”
Section: Study Characteristicsmentioning
confidence: 99%